Can Conversing with a Computer Increase Turnout? Mobilization Using Chatbot Communication. Issue 1 (23rd March 2021) - Mann, Christopher B.
Abstract: According to the burgeoning voter mobilization field experiments literature, impersonal contact has little-to-no effect. A conversation with a computer is, by definition, an impersonal interaction. However, chatbots are form of communication wherein a computer imitates conversations by interacting using natural language. Human-to-chatbot interactions are often perceived as similar to human-to-human interactions. How ubiquitous are chatbots? Just ask Siri, Cortana, Bixby, or Alexa, or ask for help on any e-commerce website (these are each chatbots). A simple voter mobilization treatment reminding users of a political chatbot (Resistbot) to vote and providing information about polling locations and hours increased turnout by 1.8 percentage points in a 2019 election. The results replicate previously unpublished field experiments by Resistbot in 2018 that found smaller but statistically significant increases in turnout.